2020
DOI: 10.3390/v12080842
|View full text |Cite
|
Sign up to set email alerts
|

Rendezvous at Plasma Membrane: Cellular Lipids and tRNA Set up Sites of HIV-1 Particle Assembly and Incorporation of Host Transmembrane Proteins

Abstract: The HIV-1 structural polyprotein Gag drives the virus particle assembly specifically at the plasma membrane (PM). During this process, the nascent virion incorporates specific subsets of cellular lipids and host membrane proteins, in addition to viral glycoproteins and viral genomic RNA. Gag binding to the PM is regulated by cellular factors, including PM-specific phospholipid PI(4,5)P2 and tRNAs, both of which bind the highly basic region in the matrix domain of Gag. In this article, we review our current und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 181 publications
(295 reference statements)
0
5
0
Order By: Relevance
“…The MA domain of HIV-1 Gag is an RNA-binding protein with a preference for binding to a variety of tRNAs in cells [ 30 ]; tRNA–MA interactions have been shown to regulate Gag-membrane association in a wide variety of in vitro and cell-based studies [ 21 , 54 ]. A recent crystal structure of the MA-tRNA Lys3 complex showed that the highly basic region (HBR) of MA interacts with tRNA at the elbow region [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MA domain of HIV-1 Gag is an RNA-binding protein with a preference for binding to a variety of tRNAs in cells [ 30 ]; tRNA–MA interactions have been shown to regulate Gag-membrane association in a wide variety of in vitro and cell-based studies [ 21 , 54 ]. A recent crystal structure of the MA-tRNA Lys3 complex showed that the highly basic region (HBR) of MA interacts with tRNA at the elbow region [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MA interacts with EPRS via the same surface with which it interacts with PI(4,5)P 2 at the PM. Although the role of tRNAs in regulating Gag-membrane association is well established [ 54 ], tRNAs in cells are almost always associated with components of the translational or tRNA-trafficking machinery and are rarely free [ 59 ]. Thus, the tRNAs that mediate viral assembly are likely bound to other proteins prior to their recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…HTLV-1 Gag is instead thought to traffic to the plasma membrane as a monomer before oligomerizing on the inner leaflet of the plasma membrane (82). The MA domain of Gag is responsible for the membrane-binding activity of the protein, which anchors the protein within lipid rafts at the plasma membrane (83)(84)(85)(86)(87). For both HIV-1 and HTLV-1, electrostatic interactions between the highly basic region of MA and phosphatidylinositol 4,5-bisphosphate [PI(4,5)P 2 ] are key regulators of membrane binding, though recent research suggests that co-translational myristoylation of the G2 position in MA is the primary driver of HTLV-1 Gag membrane binding (88,89).…”
Section: Assembly Budding and Maturationmentioning
confidence: 99%
“…This acidic entity could be a cluster of acidic lipids in the inner leaflet of the plasma membrane, such as phosphatidylinositol-(4,5)-bisphosphate (PI(4,5)P 2 ) or phosphatidylserine (PS). Gag can recruit acidic lipids to the virus assembly site via MA [31][32][33], and the MA HBR binds to both PI(4,5)P 2 [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and PS [49][50][51]. In addition, Gag multimerization facilitates PI(4,5)P 2 clustering [32,52].…”
Section: Mechanism(s) That Promote the Virion Incorporation Of Psgl-1 Cd43 And Cd44mentioning
confidence: 99%
“…These observations support the possibility that a cluster of PI(4,5)P 2 mediates the association between the MA HBR and CD44. In addition to acidic lipids, polynucleotides including tRNAs are another candidate that could link Gag and PSGL-1, CD43, and/or CD44 because the MA HBR also interacts with RNA [41,47,48,[54][55][56][57][58][59][60][61]. Identifying the acidic entity mediating the association of Gag and these uropod-directed proteins warrants future investigation.…”
Section: Mechanism(s) That Promote the Virion Incorporation Of Psgl-1 Cd43 And Cd44mentioning
confidence: 99%